Covid-19 and Technological Disruption in Health Care Delivery in England - Louise Dalingwater (Revue Française de Civilisation Britannique)
Significant progress in health care in recent years offers the potential for transforming health care provision in the form of Technology-Enabled Care (TEC) and Artificial Intelligence (AI) for diagnosis. In Britain, the National Health Service (NHS) has used technology for many years with the first scans provided by the public health service in the 1970s. Given recent advances in health technology, the Department of Health set the target of achieving a fully-digitalised NHS by 2024. Yet until the Covid-19 crisis the disruption of this sector was less marked than in other industries. The pandemic has brought the necessary impetus to increase the use of technology in this sector. Digital technologies have played a crucial role in monitoring and protecting populations against the disease. Online medical consultations have been vital in providing safe and convenient access to routine care, especially for vulnerable populations and to avoid risks to exposure to the disease. But recent advances in health care delivery have also underlined some significant challenges. The public health care system in Britain has encountered limits to the provision of a fully digitalised service: inadequate funding and outdated infrastructure. Moreover, there is often reluctance on the part of the patient and health care provider to accept digital health services. While digital health care should enable a more inclusive health service, it can also exclude vulnerable and socially disadvantaged populations. There is also an increased privacy risk when health data is digitalised. There are thus significant governance and infrastructure issues in the delivery of health care via digital devices, which this paper will explore. It will specifically focus on digital exclusion more than specific analysis of AI in health care in England and offer a literature review, which is timely given the extent of digital disruption in the wake of the health crisis.